The Relative Handgrip Strength and Risk of Cardiometabolic Disorders: A Prospective Study - Hao, Guang; Chen, Haiyan; Ying, Yuting; Wu, Min; Yang, Guang; Jing, Chunxia (Frontiers in Physiology, 2020)
Background: The aim of this study is to investigate the association between handgrip strength (HGS) and cardiometabolic disorders (CMD), including hypertension, diabetes, and dyslipidemia, in a prospective study. Methods: The association between HGS and CMD was examined using the data from 5,271 Chinese adult participants ≥ 45 years old enrolled in the CHARLS (Chinese Health and Retirement Prospective Cohort Study) in 2011-2015. Relative HGS, calculated as maximal absolute HGS from both hands divided by body mass index, was used in the primary analysis and divided into three groups according to the tertiles (weak, moderate and strong group). Results: The participants with strong HGS had a significantly lower risk of hypertension, diabetes, and dyslipidemia than those with weak HGS (P for trend <0.001). The adjusted odds ratio (OR) of participants with moderate HGS was 0.73(95% CI =0.60-0.89, P=0.002), with strong HGS was 0.66 (95%CI=0.52-0.85, P =0.001) for hypertension; the adjusted OR of participants with moderate HGS was 0.64(95% CI =0.50-0.82, P<0.001), with strong HGS was 0.46 (95%CI=0.33-0.64, P <0.001) for diabetes; and the adjusted OR of participants with moderate HGS was 0.72(95% CI =0.61-0.84, P<0.001), with strong HGS was 0.56(95% CI =0.46-0.70, P <0.001) for dyslipidemia. However, we did not find an association between absolute HGS and CMD. Conclusions: A consistent association was observed between strong relative HGS and lower risk of CMD. Further research is required to evaluate whether relative HGS can be a convincing predictor for the occurrence of CMD, and as a target for intervention in the high-risk population.